1983
DOI: 10.1148/radiology.146.3.6828682
|View full text |Cite
|
Sign up to set email alerts
|

The use of glucagon in hydrostatic reduction of intussusception: a double-blind study of 30 patients.

Abstract: Thirty patients were referred for hydrostatic reduction of ileocolic intussusception. Children with suspected gangrenous bowel or sensitivity to glucagon were excluded from the investigation. A standard protocol for the procedure was used in all patients, including the intravenous administration of glucagon or placebo (0.05 mg/kg) when the intussusception was encountered. Successful reduction was achieved in 53% of both control and glucagon-treated patients. Analysis of the length of the procedure and the ease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Glucagon has muscle relaxant effects as well as Buscopan, and has been used for enema reduction. In earlier reports, the reduction rate was higher when Glucagon was used 80,82 (level 3b); however, more recent randomized controlled studies have shown that glucagon is of no benefit 84,85 (level 2b). The use of glucagon is not recommended as it is an expensive drug in comparison to Buscopan, and health insurance in Japan may not cover the fee.…”
Section: Treatmentmentioning
confidence: 93%
“…Glucagon has muscle relaxant effects as well as Buscopan, and has been used for enema reduction. In earlier reports, the reduction rate was higher when Glucagon was used 80,82 (level 3b); however, more recent randomized controlled studies have shown that glucagon is of no benefit 84,85 (level 2b). The use of glucagon is not recommended as it is an expensive drug in comparison to Buscopan, and health insurance in Japan may not cover the fee.…”
Section: Treatmentmentioning
confidence: 93%
“…The effect of sedation on outcome is controversial: some studies reported a lower reduction rate [18], while others found a higher rate of success with sedation [31]. A recent paper reports excellent success with propofol, perhaps secondary to long-lasting bowel relaxation [32], while glucagon did not confer any benefit in two independent studies [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Our institution does not use sedation during enema reduction attempts; however, the literature lacks conclusive data about the efficacy of sedation in aiding attempts at enema reduction. 6,[13][14][15][16] There was a 14.1% referral rate (n ¼ 19) for our intussusception patients, for which patients initially diagnosed at a referring institution were transferred to our hospital for definitive care. These transfers from the community predispose these patients to a longer duration of symptoms and delay in intervention which may affect success of a primary reduction, although data are inconsistent in determining if longer duration of symptoms affects the rate of successful enema reduction.…”
Section: Discussionmentioning
confidence: 99%